Strategy of Islamic Educational Leadership in Facing the Challenges of the Digital Era at STIT Madina Sragen - sukamdi, sukamdi (Jurnal Ilmiah Mandala Education (JIME), 2025)
Introduction:The digital era has brought significant changes across various aspects of life, including the field of education. Amid the accelerating currents of globalization and digitalization, Islamic educational institutions face increasingly complex challenges, including STIT Madina Sragen. Adaptive, visionary, and innovative leadership strategies in Islamic education have become a key factor in responding to these dynamics.Materials and Methods:This study aims to analyze the Islamic educational leadership strategies implemented at STIT Madina Sragen in addressing the challenges of the digital era. A qualitative descriptive method was employed to allow an in-depth exploration of the phenomena and to identify various factors that influence leadership effectiveness within the context of Islamic education.Results:The research findings reveal that leadership grounded in a strategic vision, the ability to collaborate with various stakeholders, and the optimal utilization of digital technology plays a crucial role in enhancing the quality and relevance of Islamic education in the digital age. These findings are expected to contribute academically to the development of leadership models in Islamic education that are more responsive to contemporary demands, and to provide strategic recommendations for other educational institutions facing similar challenges.Conclusion:Based on the findings, it can be concluded that the Islamic educational leadership strategy at STIT Madina Sragen, which is responsive to digital-era developments, is supported by three main pillars: a clearly directed long-term vision, the ability to build synergy with relevant stakeholders, and the effective use of digital technology in managerial and instructional processes. This approach has proven to contribute to the improvement of institutional quality and relevance in facing changing times. Therefore, this leadership model can serve as a strategic reference for other Islamic educational institutions in responding to the challenges of globalization and technological advancement.